Fannie Lou Hamer's Revolutionary Practical Theology : Racial and Environmental Justice Concerns - Crozier, Karen D. (Theology in Practice, 2020)
In Fannie Lou Hamer's Revolutionary Practical Theology Crozier acknowledges, analyses, and constructs the civil and human rights leader's Christian thought and practice. Commonly known for her political activism, Hamer is presented as a religious thought leader whose embodiment of ideas and ideals helped to disrupt and transform the Jim Crow of the South within and beyond electoral politics. Through primary source documents of Hamer's oral history interviews, autobiographical writings, speeches, and multimedia publications on or about her life and legacy, Crozier allows Hamer to have her say on racial and environmental justice concerns. Crozier introduces Hamer as a revolutionary practical theologian who resided on the margins of the church, academy, and society.